Electrochemical Characterization of the Free Radical Scavenging of Baicalein. (12th June 2016) - Wang, Guo-Ying; Lei, Xin-Ming; Liu, Hai-Xiao; Shi, Zhe-Ru; Su, Jin-Mei; Miao, Jian; Shi, Gao-Feng
ABSTRACT: Electrochemical characterization of the free radical scavenging of baicalein was performed. A sensitive and selective electrochemical sensor for the characterization of the reaction between free radicals and baicalein was fabricated based on a nanoaluminum oxide modified carbon paste electrode. The modified carbon paste electrode showed excellent electrocatalytic activity for the characterization of free radical scavenging capacity of baicalein. In 0.2 M phosphate buffer at pH 7.4, a pair of well-defined cyclic voltammetric oxidation peaks of baicalein appeared with the maximum at 700 mv. The superoxide anion radical, hydroxyl radical, lipid peroxyl radical, and of 2, 2-diphenyl-l-picrylhydrazyl were used for investigating the free radical scavenging of baicalein. Baicalein showed varying scavenging capacities to these free radicals. The scavenging capacity of baicalein with the hydroxyl radical was the highest, followed by baicalein with the lipid peroxyl radical, 2, 2-diphenyl-l-picrylhydrazyl, and the superoxide anion radical.